"Those born in godforsaken years . . .". Issue 6 (2nd November 2021) - Dobrokhotov, Aleksandr L.
ABSTRACT: Against the backdrop of the fate of the generation that peaked between the 1970s and 1990s, this article discusses the possibility of linking times of disintegration even when the machine of a powerful and seemingly eternal empire was working at "rupturing" them. The author highlights the features of the "philosophical generation" of the last third of the twentieth century in the context of his own personal experience, the cultural characteristics of the late Soviet era, the functioning of cultural institutions, and dialogue and interaction between generations. He sees a characteristic feature of this generation as the dominance of history of philosophy, under which auspices the process of comprehending the acute problems of our own times often took place. The article argues that intergenerational dialogue can take place even in conditions created by state ideological policy for purposefully isolating individuals and groups both from each other and from the contemporary international community. Special attention is devoted to the phenomenon of "culturology, " a science that was, on the one hand, an artificial product of "perestroika, " but on the other hand, the result of productive attempts to overcome our separation from global culture, to integrate the human knowledge accumulated in previous eras into a kind of holistic understanding. The mirror of culturology reflected entire dynamics of generations at the end of the twentieth century.